Beltraniopsis rhombispora and Hemibeltrania decorosa from leaf litter in the Atlantic Forest in southern Bahia, Brazil - Santos,Marcos Vinícius Oliveira dos (2016)
Abstract Species of the Beltrania group are constantly identified in association with a variety of plant debris in Brazil and different localities of the world. Leaf litter samples of Myrcia splendens and Pera glabrata were collected in the Reserva Biológica de Una, municipality of Una, Bahia state, Brazil, in August 2012, and incubated in moist chambers. Two specimens related to Beltrania group were isolated and identified by morphological criteria. This study aimed to describe and illustrate Beltraniopsis rhombispora for the first time in Brazil. Hemibeltrania decorosa previously reported from Caatinga Biome, Bahia state, has been cited for the first time for Atlantic Forest.